Implementasi Sistem Analisis Beban Kerja Berbasis Elektronik (E-ABK) di Kecamatan Pakal Kota Surabaya - Dhea Roesita Rahmasari; Eva Hany Fanida (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
Implementation of an Electronic-Based Workload Analysis System (E-ABK) in Pakal District, Surabaya City aims to increase the efficiency and effectiveness of employee workload management in supporting public services. This research aims to determine the implementation of the Electronic Based Workload Analysis (E-ABK) system in Pakal District, Surabaya City. This research uses a descriptive method with a qualitative approach with data collection techniques through interviews, observation and documentation. The research focus uses four factors for the success of E-Government implementation: coordination, cooperation, responsibility sharing, communication. The research results show that although the E-ABK website helps in managing and calculating workload analysis, there are still obstacles in its use. Coordination, coordination is quite good but still less effective due to differences in the level of understanding of employees which hinders the coordination process. Cooperation, cooperation between related parties has been going well. Responsibility sharing, the division of responsibilities or workload is in accordance with each task. Communication, open communication regarding the implementation of the E-ABK website still has obstacles, especially in the ineffective delivery of information and differences in the level of employee understanding.